Software Component Development Based on the Mediator Pattern Design: The Interactive Graphic Organizer Case - Lopez-Villarroel, M; Ponce-Arias, H; Almarza-Menjiba, F (2011)
This article presents the redesign of a software application denominated interactive graphic organizer (IGO) using a software component architecture and the mediator pattern design. The original IGO application presented high level of coupling and primitive communication interface which generated problems in the composition of more complex software applications. The main results were a new IGO version that fulfills the characteristics associated with software components, in particular, a robust interface; and mainly, a low coupling level derived from the use of the mediator pattern design. This new version has permitted the reuse of the IGO in the composition of more complex applications. © 2005 IEEE.